Role of Neuro-Immune Cross-Talk in the Anti-obesity Effect of Electro-Acupuncture - Lu, Mengjiang; He, Yan; Gong, Meirong; Li, Qian; Tang, Qianqian; Wang, Xuan; Wang, Yaling; Yuan, Mengqian; Yu, Zhi; Xu, Bin (Frontiers in Neuroscience, 2020)
There is evidence to show that electro-acupuncture (EA) has a promotive effect on both lipolysis and thermogenesis, and that these mechanisms underlie the anti-obesity effect of EA. The sympathetic nervous system (SNS) is known to play a role in thermogenesis. Additionally, obesity is characterized by a chronic low-grade inflammatory state. Based on these findings, the aim of the present study is to investigate the potential neuro-immune mechanisms underlying the therapeutic effect of EA in obesity. In the experiment, we used a high fat diet (HFD) rats model to study the effect of EA in reducing body weight. EA increases the activity of sympathetic nerves in inguinal white adipose tissue (iWAT), especially in the HFD group. Compared to HFD rats, EA can decrease sympathetic associated macrophage (SAM) and the level of norepinephrine transporter protein (Slc6a2). The relative uncoupling protein 1 expression shows EA increases thermogenesis in iWAT, and increases β3 receptors. Interestingly, injecting β antagonist in iWAT increases Slc6a2 protein levels. Additionally, the SNS-macrophage cross-talk response to EA showed in iWAT but not in epididymis white adipose tissue. The results of the present study indicate that EA exerts its anti-obesity effect via three mechanisms: (1) inhibition of SAMs and the norepinephrine transporter protein SlC6a2, (2) promoting SNS activity and thermogenesis, and (3) regulating immunologic balance.